The Problem of Higher College Tuition - Eckstein, Otto (The Review of Economics and Statistics, 1960)
Otto Eckstein, The Problem of Higher College Tuition, The Review of Economics and Statistics, Vol. 42, No. 3, Part 2. Higher Education in the United States: The Economic Problems (Aug., 1960), pp. 61-72